An Analysis of the Education Decentralization Policy in Malawi. Issue 1 (January 2017) - Thomas, Kafumbu Fatsani
This article makes an assessment on the implementation of the decentralization policy in education in Malawi in relation to the achievement of its objectives. To bring this into perspective, the socioeconomic, legal and political contexts, and the related policies, which have a bearing on education decentralization, have been analyzed. The decentralization of education in Malawi has to a great extent been unable to meet its objectives as a result of reluctance of the central ministry to cede more decision-making power to the local level, and due to insufficient human resources. The article concludes by giving policy recommendations.